Sustainability and people in international management : 21st century challenges - Volfová, Jitka, 1982- (VŠE, Nakladatelství Oeconomica, 2025)
This scientific monograph describes new research findings on chosen International Management challenges connected to Human Resources and Sustainable Work Environment in the 21st century. It mentions best practices for managers and leaders who can get inspired when creating a sustainable working environment, treating people in organisations sustainably, and being ready to report about it. Just as we invest in and care for natural resources, it is crucial to care about human resources responsibly.